An experimental investigation of blocking by partial barriers in a rotating baroclinic annulus. Issue 2 (4th March 2018) - Marshall, S. D.; Read, P. L.
Abstract: We present a series of experimental investigations in which a differentially-heated annulus was used to investigate the effects of topography on rotating, stratified flows with similarities to the Earth's atmospheric or oceanic circulation. In particular, we compare and investigate blocking effects via partial mechanical barriers to previous experiments by the authors utilising azimuthally-periodic topography. The mechanical obstacle used was an isolated ridge, forming a partial barrier, employed to study the difference between partially blocked and fully unblocked flow. The topography was found to lead to the formation of bottom-trapped waves, as well as impacting the circulation at a level much higher than the top of the ridge. This produced a unique flow structure when the drifting flow and the topography interacted in the form of an "interference" regime at low Taylor number, but forming an erratic "irregular" regime at higher Taylor number. The results also showed evidence of resonant wave-triads, similar to those noted with periodic wavenumber-3 topography by Marshall and Read ( Geophys. Astrophys. Fluid Dyn., 2015, 109 ), though the component wavenumbers of the wave-triads and their impact on the flow were found to depend on the topography in question. With periodic topography, wave-triads were found to occur between both the baroclinic and barotropic components of the zonal wavenumber-3 mode and the wavenumber-6 baroclinic component, whereas with the partial barrier two nonlinear resonant wave-triads were noted, each sharing a common wavenumber-1 mode.